2013
DOI: 10.20533/ijds.2040.2570.2013.0091
|View full text |Cite
|
Sign up to set email alerts
|

Do Privacy and Enjoyment Matter in Personalized Services?

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Additionally, it is a significant factor in consumers' shopping motivations (Gomez et al ., 2012). Previous studies have demonstrated that the level of enjoyment experienced during the shopping process notably influences consumer behavior (Pappas et al ., 2012) in the context of brick-and-mortar stores. During shopping, individuals may experience a notable sensation of gratification and entertainment (Agarwal and Sahu, 2022; Shannon and Mandhachitara, 2008).…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…Additionally, it is a significant factor in consumers' shopping motivations (Gomez et al ., 2012). Previous studies have demonstrated that the level of enjoyment experienced during the shopping process notably influences consumer behavior (Pappas et al ., 2012) in the context of brick-and-mortar stores. During shopping, individuals may experience a notable sensation of gratification and entertainment (Agarwal and Sahu, 2022; Shannon and Mandhachitara, 2008).…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…Personalized Recommendations: Based on the user's preferences for shop type, cuisine type, and price range, the recommendation system should generate a list of relevant options. These recommendations can include nearby shops, restaurants, or products that align with the user's preferences [9][10][11][12]. Presentation of Recommendations: Present the recommended options to the user in a visually appealing and user-friendly manner.…”
Section: Implementation Initializationmentioning
confidence: 99%
“…In traditional brick-and-mortar retailing, the focus of personalization is on social interactions between service employees and their customers to generate positive psychological responses (Pappas, Giannakos, & Chrissikopoulos, 2013). In this situation, besides forming a rapport from warm welcoming, small talk, or eye contact, personalized experiences at various other service levels are not available, because of the limited technological support in traditional retailing.…”
Section: Literature Review Personalization and Privacymentioning
confidence: 99%